IMPLEMENTASI METODE EXTREME PROGRAMMING UNTUK PERANCANGAN APLIKASI SISTEM INFORMASI PADA KOPERASI SIMPAN PINJAM BERBASIS WEB (STUDI KASUS: KOPERASI JAMA’AH MASJID INDONESIA) - Ahmad Muhlisin; Dola Irwanto (CV. Multi Kreasi Media, 2022)
Along with the times and increasingly sophisticated technology, driven by science in the field of information technology, it can affect the activities of a company, both large and small. Cooperatives are an important organization to increase the economic growth of the community. One alternative for the community to get funds to develop their business or in an effort to fulfill their daily needs is through the Savings and Loans Cooperative. To improve savings and loan services better for members, better data handling and processing are needed. From the results of the analysis carried out on the system that has been running so far used by the Indonesian Mosque Jama'ah Cooperative (KJMI) it is inadequate for the desired system needs. In providing its services to members, it still uses a manual system in its administration which includes input, storage of deposit data, loan data and installment data, as well as desired report data such as deposit data reports and loan data reports. The purpose of this research is to design and develop a Savings and Loans Information System for the Indonesian Mosque Jama'ah Cooperative (KJMI) which can help simplify and speed up the process of collecting data on deposits, loans, withdrawals and installments. Using the PHP programming language, Unified Modeling Language (UML) and MySql database with the Extreme Programming development method. From the results of research and discussion on the design of this system application, the required reports can be printed, making it easier and faster to make decisions.